2018
DOI: 10.1371/journal.pone.0197965
|View full text |Cite
|
Sign up to set email alerts
|

Bone density of the femoral neck in patients on maintenance dialysis

Abstract: BackgroundOur institution recently started using the femoral neck (FN), as well as the non-shunted distal radius (Rd), to measure bone mineral density (BMD) in patients with chronic kidney disease. We examined the utility and characteristics of this measurement in patients on maintenance dialysis.MethodsWe selected 293 patients on chronic dialysis. We measured Rd and FN BMD using dual-energy X-ray absorptiometry, and we reviewed blood test findings, which included hemoglobin, albumin, blood urea nitrogen, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, although bone metabolism-related makers were not associated with BMD, SMI was independently associated with BMD. A previous study reported that the femoral neck BMD was affected by body weight and serum creatinine level, which could reflect muscle mass (19). Therefore, the maintenance of skeletal muscle might be important in preventing BMD.…”
Section: Discussionmentioning
confidence: 97%
“…However, although bone metabolism-related makers were not associated with BMD, SMI was independently associated with BMD. A previous study reported that the femoral neck BMD was affected by body weight and serum creatinine level, which could reflect muscle mass (19). Therefore, the maintenance of skeletal muscle might be important in preventing BMD.…”
Section: Discussionmentioning
confidence: 97%
“…We also analyzed each component of MetS and the associations with T-score, and found that abdominal obesity, hypertriglyceridemia, low HDL-C, and hyperglycemia were associated with T-score, whereas high blood pressure was not. Patients undergoing chronic dialysis have a lower BMD than healthy subjects of similar age due to CKD-related mineral and bone disorders [ 45 ]. Abdominal obesity can reflect higher mechanical loading on the bone, which then stimulates bone accrual [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, feelings of shame, low self-esteem and stress caused by negative perceptions of body image may lead to eating disorders with further detriment to QOL (McDermott et al 2015). Bone mineral density in dialysis-dependent patients is also significantly lower than for the general population, and in younger patients, this frailty could be a serious hindrance to pursuing their personal aspirations (Nakanishi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conditions that dialysis patients may suffer from are: osteoarthritis, fractures and osteonecrosis, which may in some cases result in total knee replacement surgery (Nakanishi et al 2018;Ottesen et al 2018).…”
Section: Discussionmentioning
confidence: 99%